The proceeding of the Inter-American Court of Human Rights regarding vulnerable groups: An analysis of Advisory Opinion 24/2017 - Hennig Leal, Mônia Clarissa (2020)
The Inter-American Human Rights System is inserted in a context of searching for the maximum protection and guarantee of human rights. Therefore, in addition to a Federal Constitution that aims to grant human and fundamental rights, there is also a Global System and a Regional Protection System, which highlights the relevance and timeliness of the matter. Based on the premise, this article studies the contents of the right of non-discrimination and equal protection before the law, especially from the logicality of the advisory role exercised by the Inter-American Court of Human Rights. This way, the following issue arises: what is the position adopted in the Advisory Opinion 24/2017 by the Inter-American Court of Human Rights, in regard to the rights of the LGBT community, as a vulnerable group? In order to solve it, the deductive approach method is used, aiming, at first, to come to the operating logic of the Inter-American System, focusing on the advisory function of the Inter-American Court; to verify the main aspects regarding the protection of vulnerable groups from the perspective of the American Convention; and, finally, to critically analyze the Advisory Opinion 24/2017, issued by the Court, which deals with the protection that should be granted by the States to the LGBT community. At last, it is concluded that the Court understands that the States must adopt protective measures towards this group, avoiding any kind of discrimination and eradicating, or at least reducing, the violence that results from gender and sexual identity.